Peranan Pemerintah Daerah Dalam Pengelolaan Sampah di Kabupaten Bone - Muh Danar Gemilang (Departemen Ilmu Pemerintahan Fisip Unhas, 2025)
Waste management is one of the major environmental issues and a key challenge in achieving sustainable development and a healthy environment. Population growth and changes in consumption patterns have led to an increase in both the volume and diversity of waste generated by society. This condition is also evident in Bone Regency, where the amount of waste produced is not proportional to the waste reduction efforts that have been implemented. This study aims to analyze the implementation of waste management in Bone Regency, focusing on the stages of waste sorting, collection, transportation, processing, and final disposal. This study employed a qualitative approach with a descriptive research method. Data were collected through observation, interviews, documentation, and literature review. The research was conducted at the Environmental Agency of Bone Regency, the Passippo Final Disposal Site (TPA), and the districts of Tanete Riattang, West Tanete Riattang, and East Tanete Riattang. The data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The findings indicate that waste management in Bone Regency has been implemented through the stages of waste sorting, collection, transportation, processing, and final disposal. Waste collection and transportation are routinely carried out by the Environmental Agency with the involvement of sanitation workers and community members. In the processing stage, the local government has developed waste bank programs as an effort to reduce waste volume and increase the economic value of recyclable materials. However, waste management still faces several challenges, including limited human resources, the increasing volume of waste generated by the community, and the continued reliance on a semi-open dumping system at the final disposal site. Therefore, greater community participation, stronger institutional capacity, and the development of a more sustainable waste management system are needed to improve environmental quality in Bone Regency.